2022
DOI: 10.1136/bmjopen-2021-056214
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone standoff: a qualitative study exploring clinician responses when a patient uses a smartphone to record a hospital clinical encounter

Abstract: ObjectivesPatients are initiating recordings of their clinical encounters using a smartphone. While this is an important, universal issue, little is known about the clinician viewpoint. Understanding clinician perspectives and behaviours is key to ensuring the protection of patient and clinician interests. This study aimed to gain a deep understanding of clinician attitudes and behaviours to patient-led recordings of hospital clinical encounters.DesignSemistructured interviews were conducted with 20 hospital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(39 citation statements)
references
References 28 publications
(106 reference statements)
1
38
0
Order By: Relevance
“…[40][41][42] Clinicians who regularly refuse recordings may need to both re-examine their practice, consult hospital guidelines as to consumer-clinician rights and consider how to mindfully communicate a refusal if that is still their preference. 3,6,13 Our findings revealed that consumers are not aware of their rights or responsibilities when it comes to recording a clinical encounter. This is both a barrier to them using a potentially beneficial tool and a reason why they may not verbally seek consent, with the potential to lead to more covert recording.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[40][41][42] Clinicians who regularly refuse recordings may need to both re-examine their practice, consult hospital guidelines as to consumer-clinician rights and consider how to mindfully communicate a refusal if that is still their preference. 3,6,13 Our findings revealed that consumers are not aware of their rights or responsibilities when it comes to recording a clinical encounter. This is both a barrier to them using a potentially beneficial tool and a reason why they may not verbally seek consent, with the potential to lead to more covert recording.…”
Section: Discussionmentioning
confidence: 75%
“…4,5,7,14 Patient-led recordings have been found to mirror the benefits of service-led recordings, which include increased recall and understanding, support for decision-making and increased patient empowerment. 5,7,[9][10][11][12] Although clinicians recognize some of the benefits of recording, 3,12,13 clinicians cite several concerns of patient-led recording, such as confidentiality risks, potential changes to the consumer-clinician dynamic and possible medico-legal ramifications, which can act as barriers to consenting to the recordings. 3,5,12 Previous studies have sought to investigate ways that recordings can be integrated into service, including the use of clinical champions 12 or the use of a smartphone app which aims to mitigate some of the medico-legal fears held by clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…7 , 8 Clinicians are, therefore, required to make difficult decisions and take actions with limited direction or training. 9 …”
Section: Introductionmentioning
confidence: 99%
“…10 Despite the relaxation of restrictions, there is an enduring fear among clinicians regarding patients using their smartphone cameras to record hospital experiences. 1 , 9 , 10 Some clinicians may decline a recording due to their own preference not to be recorded, others due to the recording being a distraction or putting the confidentiality of others at risk. 9 Covert recording is of particular concern to clinicians, who are reported to hold mainly negative attitudes due to medico-legal implications, fear regarding loss of control of the encounter and material, and confidentiality issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation